A INFLUÊNCIA DA EDUCAÇÃO DE BASE COMO INSTRUMENTO PARA A REDUÇÃO DE ACIDENTES DO TRABALHO - Balthazar Junior, Celso (2004)
Considering human factor as the main cause of on the job accidents, as well as a central element in its prevention and control and also assuming that an accidents prevention directed education level influences behavior when it faces job intrinsic risks, a research and it s respective analysis were conducted, in this dissertation, over the base education curriculum in order to find collaborating elements for students formation as citizens able to naturally prevent accidents just as a single citizenship act. So, it was necessary to get acquainted to and to analyze part of it s specific legislation as much as some rules from the Ministério da Educcção orientations for the fundamental, medium, professional and superior education levels. A company s five year period of on the job accidents records, were analyzed with the purpose of investigating a possible large number of accidents involving employees from the same education area, and so obtaining as product the justification for the principal question in this dissertation about scholar formation influence. As complement for the analysis cited on the above paragraph a 82 occupational activities description was taken on the brazilian occupation classification edited by the Job and Work Ministry. A contradiction was established by comparison between these descriptions and the significant statistical number of accidents involving employees from the human science area, in opposition to the non risk evidence found in the descriptions for this area. The knowledge of all researched data drove this study to the analyzed company employees profile. The lack of better relationship between Ministério da Educação and Ministério do Trabalho e Emprego, due to their work world goal convergence, was observed through data obtained in this research. Due to difficulties found during data research about the analyzed company s registered accidents it wasn t possible to precisely establish a connection between the data indicated in this dissertation and the learning process. Due to prescriptions related to students preparation for work world found in the specific legislation, a brand new opportunity is revealed for prominence educational designs not only for on the job accidents reducing but even on the off the job accidents.